2018
DOI: 10.7567/jjap.57.045003
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable field emission from ZnO nanowire field emitters controlled by an amorphous indium–gallium–zinc-oxide thin film transistor

Abstract: Lowering the driving voltage and improving the stability of nanowire field emitters are essential for them to be applied in devices. In this study the characteristics of zinc oxide (ZnO) nanowire field emitter arrays (FEAs) controlled by an amorphous indium–gallium–zinc-oxide thin film transistor (a-IGZO TFT) were studied. A low driving voltage along with stabilization of the field emission current were achieved. Modulation of field emission currents up to three orders of magnitude was achieved at a gate volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The stability is another important issue for the application of a cold cathode. Although a cascade structure by which the ZnO nanowires are connected with a TFT [ 57 ] or MOSFET [ 58 ] in series can improve the stability of the device, this review mainly concerns the intrinsic stability of the cathode, which can give a better comparison with other cold cathode materials. So far, it has been found that the fluctuation of emission current of ZnO nanowires film can be as low as 1–2% during the long-term test for over 3 h [ 38 , 46 , 59 ].…”
Section: Field Emissionmentioning
confidence: 99%
“…The stability is another important issue for the application of a cold cathode. Although a cascade structure by which the ZnO nanowires are connected with a TFT [ 57 ] or MOSFET [ 58 ] in series can improve the stability of the device, this review mainly concerns the intrinsic stability of the cathode, which can give a better comparison with other cold cathode materials. So far, it has been found that the fluctuation of emission current of ZnO nanowires film can be as low as 1–2% during the long-term test for over 3 h [ 38 , 46 , 59 ].…”
Section: Field Emissionmentioning
confidence: 99%
“…With a high breakdown field, more emitters can be activated when increasing the applied field. One could also make better use of the ballasting effect usually existing in the ZnO nanowire field emitter itself [ 5 ] or equipped with an active driving device [ 17–18 ] and thus a highly uniform stable emission and a high emission current could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Thin film transistors (TFTs) are widely used as active driving components for displays, image sensors, etc. However, many applications require operation voltages as high as hundred volts, such as ferroelectric liquid crystals, large area direct conversion X-ray imaging sensor, field emitter arrays, and integrated MEMS [1][2][3][4][5]. Usually a highvoltage TFTs are needed in those applications.…”
mentioning
confidence: 99%
“…The distance between the two voltage probes (V1, V2) is 30 μm and the probe 1 to source electrode distance (X1) is 30 μm. The length of probes is designed to avoid the shunting effect that may cause errors [5]. In 3probe HV TFT, the gate edge aligns with the edge of the probe.…”
mentioning
confidence: 99%